Yield Potential of Long Bearing Shoots of Ten Plum Cultivars (Prunus domestica L.) - Mićić Nikola; Đurić Gordana; Životić Aleksandar (Agroznanje, 2015)
The yield potential of ten plum cultivars ('Čačak's Beauty', 'Čačak's Best', 'Čačak's Fruitful', 'California Blue', 'Elena', 'Hanita', 'Katinka', 'Renclode Althan', 'Stanley', and 'Top'), exhibited through the structure of buds on long bearing shoots, was analyzed under the agro-ecological growing conditions of the Banja Luka region for two fruiting seasons (2012 and 2013). Long bearing shoots with collateral buds were the most productive type of fruiting branches, which is why the structure of buds on these branches is the basis for defining specific cultural measures in order to boost yield potential. Based on the established structure of buds on the nodes along the long bearing shoots and the established yield potential, the plum cultivars evaluated were classified into 4 groups: 1) cultivars with a predisposition to have a high yield potential, without need for specific treatments in fruiting control ('Čačak's Beauty' and 'Top'); 2) cultivars with a predisposition to have a high yield potential with the application of cultivar-specific cultural measures for control of fruiting ('Čačak's Best', 'Elena', and 'Stanley'); 3) cultivars that require differentiated cultural measures in the control of yield potential for regular fruiting ('Čačak's Fruitful', 'California Blue', and 'Katinka') and 4) cultivars that require innovative growing systems and specific cultural treatments to control fruiting ('Hanita' and 'Renclode Althan').